The emergence of Klebsiella pneumoniae liver abscess in non-diabetic patients and the distribution of capsular types. Issue 1 (December 2016) - Chuang, Chien; Fan, Wen-Chien; Lin, Yi-Tsung; Wang, Fu-Der
Abstract Background Klebsiella pneumoniae is the most common pathogen of community-acquired pyogenic liver abscess in East Asia. Diabetes mellitus (DM) is a well-established risk factor forK. pneumoniae liver abscess (KPLA). However, reports regarding the emergence of KPLA in non-diabetic patients are limited. Results A total 230 patients with KPLA from a medical center in Taiwan were identified retrospectively. The rate of DM in patients with KPLA was 44.4 % in 2011, 57.9 % in 2012, 44.9 % in 2013, 35.0 % in 2014, and 53.5 % in 2015. Diabetic patients had higher rate of gas-forming abscesses than non-diabetic patients, but the clinical outcomes were not different. The six virulent capsular types (K1, K2, K5, K20, K54, and K57) accounted for 90.2 % of allK. pneumoniae isolates, and were more prevalent in non-diabetic than diabetic patients (93.9 vs 85.9 %, P  = 0.048). The six virulent capsular types were also more prevalent in the group with optimal glycemic levels (Non-DM and DM with HbA1c level <7 %) than the DM group with HbA1c level ≥7 % (93.9 vs 84.3 %, P  = 0.022). Conclusion Klebsiella pneumoniae liver abscess has emerged in non-diabetic patients in Taiwan. Diabetic patients were at higher risk of acquiring gas-forming abscesses. Non diabetic patients and diabetic patients with optimal glycemic levels are more susceptible to the virulent capsular types ofK. pneumoniae .